Assessing the impact of synoptic weather systems on air quality in Sydney using Radon 222. (15th February 2023) - Crawford, Jagoda; Chambers, Scott D.; Williams, Alastair G.
Abstract: The state of the atmosphere can affect the degree of dilution of emitted pollutants, and similar local and diurnal meteorological conditions can be grouped according to prevailing synoptic scale weather systems. Traditionally, various methods have been used to classify atmospheric conditions. Here we investigate the use of Radon-222 (radon) for the classification of weather systems and determine the degree of dilution under different synoptic conditions. Air quality data was analyzed in Richmond Australia over a 13-year period. Radon was used to determine 5 nocturnal stability categories numbered 0 to 4, with 0 capturing times of fast-changing fetch influences, and 1–4 representing increasing conditions of nocturnal stability (1: near neutral, to 4: strongly stable). These categories were then related to prevailing synoptic weather systems. It was found that increasing radon-derived stability categories were associated with reducing intensity of frontal systems traversing southern Australia and extending into the Southern Ocean, with stability category 4 associated with blocking high pressure systems located to the east of the site. The median nocturnal wind speeds and mixing layer heights decreased as we moved from stability category 0 to 4, indicating that the mixing volumes for pollutants released into the atmosphere from surface sources was progressively getting smaller. This decreasing dilution from stability category 0 to 4 resulted in strongly increasing median pollutant concentrations. However, on diurnal and seasonal time scales, differences were observed which could be attributed to changes in emission rates. Our results show that when investigating the impact of air quality mitigation strategies, any variations in meteorological conditions during the comparison periods needs to be considered in addition to changes in pollution emission rates, and that near-surface radon observations and the ventilation coefficient are a convenient and effective tool for this purpose. Highlights: Radon-222 was used to determine atmospheric stability categories. The Radon-222 stability categories identified separate synoptic weather systems. Degree of dilution of pollutants was quantified using the ventilation coefficient. Variation in atmospheric conditions need to be considered in air quality studies.